MEANING ACCURACIES AND INACCURACIES IN TITANIC'S INDONESIAN SUBTITLES - Achmad Basari (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2009)
Nowadays, there are more and more chances for movie maniacs to satisfy their great interest to watch over different kinds of film genre every time and everywhere. They can easily get them atVideo rental and watch them at home or go to Cineplex as they wish. From the foreign film screen, they see subtitles. Usually the film audiences watch it without thinking seriously about the accurate or inaccurate subtitles. In fact, subtitle is the key to understand the meaning of the contents in foreign languages. However, it is impossible to deny that film translators are not always professional ones. They sometimes make unnecessary inaccurate meanings in film subtitling as likely found in several foreign movies shown in Indonesia. This article will guide the readership to find out that in such a worldclass and famous movie like Titanic, accuracy and inaccuracy of its subtitles are surprisingly found.Keywords: subtitles, accurate, inaccurate, film audience, contextualmeaning